Revascularization After Traumatic Spinal Cord Injury - Yao, Chun; Cao, Xuemin; Yu, Bin (Frontiers in Physiology, 2021)
Traumatic spinal cord injury (SCI) is a complex pathological process. The initial mechanical damage is followed by a progressive secondary injury cascade. The injury ruptures the local microvasculature and disturbs blood-spinal cord barriers, exacerbating inflammation and tissue damage. Although endogenous angiogenesis is triggered, the new vessels are insufficient and often fail to function normally. Numerous blood vessel interventions, such as proangiogenic factor administration, gene modulation, cell transplantation, biomaterial implantation, and physical stimulation, have been applied as SCI treatments. Here, we briefly describe alterations and effects of the vascular system on local microenvironments after SCI. Therapies targeted at revascularization for SCI are also summarized.